(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the clinical and epidemiological characteristics, prevalence of metastasis, and factors associated with metastasis in colorectal cancer patients at Ca Mau General Hospital during 2020–2024. Methods: A retrospective cross-sectional study was conducted on 781 patients with colorectal cancer diagnosed and treated from 2020 to 2024. Data were extracted from medical records and the hospital management system. Tumor location was classified into two anatomical groups: colon and rectum. Associations were measured using odds ratios (ORs). Generalized Structural Equation Modeling (GSEM) with a logit link was used as an exploratory hypothetical model. Data analysis was performed using STATA 18.0. Results: The prevalence of metastasis was 70.81%. The liver was the most common metastatic site (53.71%), followed by the lungs (25.86%) and bones (12.12%). Rectal tumors were associated with a higher likelihood of metastasis than colonic tumors (OR=2.15; 95%CI: 1.52–3.02). Anemia (OR=2.85; 95%CI: 2.04–3.89) and intestinal obstruction (OR=2.17; 95%CI: 1.61–3.03) were also significantly associated with metastasis. In the exploratory GSEM, urban residence was associated with lower odds of metastasis through both direct and indirect paths via time from confirmed diagnosis to the most recent recorded assessment (total OR=0.60; 95%CI: 0.40–0.84). Conclusions: Metastasis among colorectal cancer patients remained high in this hospital-based sample. Tumor location, anemia, and intestinal obstruction were associated with metastatic disease. Exploratory GSEM suggested a potential pathway involving place of residence and disease-course indicators.